Effectiveness of Influenza Vaccination of Pregnant Women for Prevention of Maternal and Early Infant Influenza-Associated Hospitalizations in South Africa: A Prospective Test-Negative Study. (19th October 2022) - Nunes, Marta C; Walaza, Sibongile; Meiring, Susan; Zar, Heather J; Reubenson, Gary; McMorrow, Meredith; Tempia, Stefano; Rossi, Liza; Itzikowitz, Raphaela; Bishop, Kate; Mathunjwa, Azwifarwi; Wise, Amy; et al.
Abstract: Background: Influenza vaccination during pregnancy reduces influenza-associated illness in the women and their infants, but effectiveness estimates against influenza-associated hospitalization are limited and lacking from settings with high human immunodeficiency virus (HIV) infection prevalence. We assessed the effect of maternal vaccination in HIV-uninfected women and women with HIV in preventing influenza-associated hospitalizations in infants and the women. Methods: During 2015–2018, influenza vaccination campaigns targeting pregnant women were augmented at selected antenatal clinics; these were coupled with prospective hospital-based surveillance for acute respiratory or febrile illness in infants aged <6 months and cardiorespiratory illness among pregnant or postpartum women. Vaccine effectiveness (VE) was assessed using a test-negative case-control study. Results: Overall, 71 influenza-positive and 371 influenza-negative infants were included in the analysis; mothers of 26.8% of influenza-positive infants were vaccinated during pregnancy compared with 35.6% of influenza-negative infants, corresponding to an adjusted VE (aVE) of 29.0% (95% confidence interval [CI], −33.6% to 62.3%). When limited to vaccine-matched strains, aVE was 65.2% (95% CI, 11.7%–86.3%). For maternal hospitalizations, 56 influenza-positive and 345 influenza-negative women were included in the analysis, with 28.6% of influenza-positive women being vaccinated compared with 38.3% of influenza-negatives, for an aVE of 46.9% (95% CI, −2.8% to 72.5%). Analysis restricted to HIV-uninfected women resulted in 82.8% (95% CI, 40.7%–95.0%) aVE. No significant aVE (−32.5% [95% CI, −208.7% to 43.1%]) was detected among women with HIV. Conclusions: Influenza vaccination during pregnancy prevented influenza-associated hospitalizations among young infants when infected with vaccine strains and among HIV-uninfected women. Abstract : Influenza vaccination during pregnancy prevented influenza-associated hospitalizations among young infants when infected with influenza vaccine strains, and among women without HIV, although, no effect was detected in women living with HIV.